Marker-assisted breeding to develop the drought-tolerant version of Sabitri, a popular variety from Nepal - Dixit, Shalabh; Yadaw, Ram Baran; Mishra, Krishna Kumar; Kumar, Arvind (Springer, 2017)
Sabitri is a rice variety grown in a large part of the rainfed areas of Nepal. It was originally developed for irrigated condition; hence, this variety suffers high yield decline under drought. Two QTLs, qDTY 3.2 and qDTY 12.1 , with large effects on grain yield under drought were identified in the Sabitri background in separate QTL mapping studies. The present study reports the development of Sabitri near isogenic lines (NILs) with combinations of these two QTLs and their characterization under drought. To do so, marker-assisted backcross breeding (MABB) was combined with phenotypic selection to develop high-yielding drought-tolerant NILs with Sabitri grain type. Apart from this, drought-tolerant variants for grain type with high yield under non-stress were identified among the developed NILs. Early days to flowering of up to 13 days and reduction in plant height of up to 13 cm as compared to Sabitri were observed in the developed NILs. Some of these NILs showed higher yield compared to Sabitri and relatively higher tolerance to drought, indicating the capture of positive alleles and interactions during the course of selection. The developed NILs possessed high yield potential which make them suitable materials for the testing of water-saving technologies in irrigated areas. Based on their performance, these NILs can be deployed in rainfed areas in Nepal and other countries of South Asia to increase yield stability.